2020
DOI: 10.1111/ijpo.12748
|View full text |Cite
|
Sign up to set email alerts
|

Association of gut microbiome with fasting triglycerides, fasting insulin and obesity status in Mexican children

Abstract: Summary Background The association of gut microbiota with obesity and its cardio‐metabolic complications in paediatric populations is still controversial. Objective We investigated the association of obesity and cardio‐metabolic traits with gut microbiota on 167 and 163 children with normal weight and obesity from Mexico City and Oaxaca, Mexico. Methods Anthropometric and biochemical traits were measured. The microbial communities were determined by high‐throughput sequencing of bacterial 16S rRNA gene v3‐v4 r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 45 publications
(47 reference statements)
3
31
0
Order By: Relevance
“…Further, depletion of Romboutsia correlated with weight loss and decreased insulin resistance, a finding which has been previously described. 23 , 24 Other works have linked Romboutsia to glycerophospholipids, which have been implicated in obesity-induced fatty liver disease. 25 Together, these findings suggest a role for Romboutsia in the modulatory effects of RYGB on glycerophospholipids.…”
Section: Discussionmentioning
confidence: 99%
“…Further, depletion of Romboutsia correlated with weight loss and decreased insulin resistance, a finding which has been previously described. 23 , 24 Other works have linked Romboutsia to glycerophospholipids, which have been implicated in obesity-induced fatty liver disease. 25 Together, these findings suggest a role for Romboutsia in the modulatory effects of RYGB on glycerophospholipids.…”
Section: Discussionmentioning
confidence: 99%
“…High F/B ratio in CS delivery infants may help explain why Mexico that had one of the highest global average annual rate increases in CS led the world in childhood obesity, which may be associated with the high F/B ratio in CS delivery infants. Also, another recent study from Mexico demonstrated that Firmicutes and Bacteroidetes phyla were positively and negatively associated with obesity, respectively ( Vazquez-Moreno et al, 2020 ). By intensively monitoring the F/B ratio at 9 time points, the CS group had a permanently higher F/B ratio than the VD group that might provide crucial evidence for the causality of high F/B ratio in the first 3 months of life and the obesity in the later life.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, studies in Mexican children showed that Ruminococcaceae UCG-002 was present in normal weighted individuals and appeared to be negatively associated with obesity but positively associated with fasting plasma insulin, highlighting the relevance of studying the role of the gut microbiota in human intermediate metabolism. 77 …”
Section: Gut Microbiota and Its Possible Relationship With Metabolic Syndromementioning
confidence: 99%